Developing self-regulatory skills and reflective practice in professional English soccer academy goalkeepers using aloud Pilot Study - Mcgreary, M.; Lawrence, J.; Whitehead, A.E. (International Journal of Sport Psychology, 2024)
Think aloud (TA) has previously been used as a tool that facilitates the development of self-regulatory and reflective practice skills in coaches and golfers (Birch et al., 2022). This pilot study aimed to further explore the use of TA as a tool to facilitate self-regulatory and reflective practice skills by expanding the scope of this research into soccer goalkeepers. Two academy goalkeepers at a professional English soccer club used TA during three separate training sessions over three weeks, listened back to their TA audio and then took part in semi-structured interviews to discuss their experiences of TA. A template analysis, involving the adoption of both inductive and deductive lenses, was undertaken, with Zimmerman and Campillo`s (2003) phases and subphases of self-regulation used as a guiding framework. The findings were organised into three themes: forethought phase, performance phase and self-reflective phase. Findings supported the use of TA as a tool to develop both self-regulatory and reflective skills in academy goalkeepers (e.g., enhanced reflective practice, increased self-monitoring). Coaching and support staff may wish to use these preliminary findings and consider the usefulness of embedding TA into their practices as one method for encouraging athletes to reflect on their thought processes supporting them to become independent and active participants in their learning process.